Перспективы применения ионозонда в составе радара некогерентного рассеяния Института ионосферы - Лысенко, В. Н.; Скляров, И. Б. (НТУ "ХПИ", 2004)
Features of automatic ionospheric stations operation jointly with IS radar are considered. The information obtained after digital processing allows to essentially increasing ionospheric data quality
Keywords: ионосфера; зондирование радиоимпульсами; сигнал; радар HP; радиоволны; диапазон; ионосферная плазма